The Efficacy of Parenteral Nutrition and Enteral Nutrition Supports in Traumatic Brain Injury: A Systemic Review and Network Meta-Analysis - Yan Qin; Maoxia Liu; Fengbao Guo; Du Chen; Peng Yang; Xionghui Chen; Feng Xu (Emergency Medicine International)
Background. Enteral nutrition (EN) is often used in patients with traumatic brain injury (TBI), but some studies have shown that EN has its disadvantages. However, it is not clear which nutritional support is appropriate to reduce mortality, improve prognosis, and improve nutritional status in patients with TBI. We performed this Bayesian network meta-analysis to evaluate the improvement of nutritional indicators and the clinical outcomes of patients with TBI. Methods. We systematically searched PubMed, Embase, Cochrane Library, and Web of Science from inception until December 2021. All randomized controlled trials (RCTs) which compared the effects of different nutritional supports on clinical outcomes and nutritional indicators in patients with TBI were included. The co-primary outcomes included mortality and the value of serum albumin. The secondary outcomes were nitrogen balance, the length of study (LOS) in the ICU, and feeding-related complications. The network meta-analysis was performed to adjust for indirect comparison and mixed treatment analysis. Results. 7 studies enroll a total of 456 patients who received different nutritional supports including parenteral nutrition (PN), enteral nutrition (EN), and PN + EN. No effects on in-hospital mortality (Median RR = 1.06, 95% Crl = 0.12 to 1.77) and the value of 0-1 days of serum albumin were found between the included regimens. However, the value of 11–13 days of serum albumin of EN was better than that of PN (WMD = −4.95, 95% CI = −7.18 to −2.72, P<0.0001, I2 = 0%), and 16–20 days of serum albumin of EN + PN was better than that of EN (WMD = −7.42, 95% CI = −14.51 to −0.34, P=0.04, I2 = 90%). No effects on the 5–7 day nitrogen balance were found between the included regimens. In addition, the complications including pneumonia and sepsis have no statistical difference between EN and PN. EN was superior to PN in terms of LOS in the ICU and the incidence rate of stress ulcers. Although the difference in indirect comparisons between the included regimens was not statistically significant, the results showed that PN seemed to rank behind other regimens, and the difference between them was extremely small. Conclusion. Available evidence suggests that EN + PN appears to be the most effective strategy for patients with TBI in improving clinical outcomes and nutritional support compared with other nutritional supports. Further trials are required.